Overcoming overtourism in Europe: towards an institutional-behavioral research agenda - Benner, Maximilian (Zeitschrift für Wirtschaftsgeographie, 2019)
A number of European tourist destinations have become the subject of a public debate on overtourism. The present article argues that problems discussed under the overtourism debate cannot be solved by limiting tourist numbers alone. Rather, the article calls for multidimensional strategies that build on a vision of qualitative tourism development shared by various coalitions of agents. Such a vision should consider which forms of tourism to encourage and which ones to discourage, and what incentives and disincentives to set. Designing and implementing these strategies raises a number of questions that can be grouped under the four dimensions of policies, organization, institutions, and behavior. Institutional approaches known from economic geography can serve to analyze the prospects of policies, and insights from behavioral economics such as the nudging approach can serve to inform policy implementation. These approaches are related to organizational and policy-related aspects of qualitative tourism development. By following the analytical framework provided by the four dimensions mentioned, the article proposes a research agenda for policy-relevant studies on curbing or preventing problems of overtourism.
Gesehen am 10.06.2022